1101 Businesses you can start from home - Hall, Daryl Allen (New York : John Wiley, 1995)
Business
Keywords: Business; Ads; Animals; Appliances; Artist; Automotive; Children; Cleaning; Crafts; Entertainment; Food; Health; Horticulture; Household; Housing; Instruction; Mail order; Manufacturing; Novelties; Pets; Photography; Printing; Real estate; Recreation; Repairs; Retail; Security; Sewing; Special services; Telephone; Travel; Typing; Vending and jobbers; Writing